MYCN-mediated overexpression of mitotic spindle regulatory genes and loss of p53-p21 function jointly support the survival of tetraploid neuroblastoma cells - Gogolin, Sina; Batra, Richa; Harder, Nathalie; Ehemann, Volker; Paffhausen, Tobias; Diessl, Nicolle; Sagulenko, Vitaliya; Benner, Axel; Gade, Stephan; Nolte, Ingo; Rohr, Karl; König, Rainer; et al. (Cancer letters, 2013)
High-risk neuroblastomas often harbor structural chromosomal alterations, including amplified MYCN, and usually have a near-di/tetraploid DNA index, but the mechanisms creating tetraploidy remain unclear. Gene-expression analyses revealed that certain MYCN/MYC and p53/pRB-E2F target genes, especially regulating mitotic processes, are strongly expressed in near-di/tetraploid neuroblastomas. Using a functional RNAi screening approach and live-cell imaging, we identified a group of genes, including MAD2L1, which after knockdown induced mitotic-linked cell death in MYCN-amplified and TP53-mutated neuroblastoma cells. We found that MYCN/MYC-mediated overactivation of the metaphase-anaphase checkpoint synergizes with loss of p53-p21 function to prevent arrest or apoptosis of tetraploid neuroblastoma cells.
Gesehen am 12.02.2020
First published: 24 November 2012